Integration of Local Cultural Values in Indonesian Language Learning for Strengthening Elementary Students’ Character: A Systematic Literature Review - Putri Hana Pebriana; Heri Kurniawan; Wadda Mahmudah; Riska Aulia; Nayya Azru Sauqi; Salsa Billah Rahman; Elvi Syahri Jasmi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study examines the integration of local cultural values into Indonesian language instruction to strengthen elementary school students’ character development. Using a Systematic Literature Review (SLR) approach, the study analyzed 25 relevant scholarly articles selected from academic databases and Google Scholar based on strict inclusion criteria. The synthesis identified effective strategies and best practices for incorporating local cultural elements such as folktales, proverbs, pantun, and oral traditions into the Indonesian language curriculum. The findings indicate that integrating local culture not only enhances students’ linguistic understanding but also fosters positive character values, including tolerance, cooperation, patriotism, responsibility, honesty, social awareness, respect for elders, and appreciation of diversity. Implementation can be carried out through thematic and contextual approaches, culture-based extracurricular activities, and the development of locally relevant teaching materials. However, challenges remain, including limited teacher competence, insufficient contextual learning resources, and inadequate policy support. Therefore, this study recommends teacher training, the development of local wisdom–based instructional materials, and collaboration among schools, families, and communities. Integrating local cultural values makes Indonesian language learning more meaningful and supports sustainable character education aligned with 21st-century learning and the Pancasila Student Profile.